Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Keputusan Lindung Nilai Pada Perusahaan Sawit Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Sahara Novatania Yasmine; Dewa Putra Krishna Mahardika (Universitas Sains dan Teknologi Komputer, 2023)
Hedging is an activity undertaken by an entity to control the risk of price changes in assets or liabilities by using derivative instruments. The study’s purpose is to interpret the liquidity, solvability, and profitability’s influences on palm companies’ hedging decisions that registered on the Indonesian Stock Exchange (IDX) in 2017-2021. The research population included 13 palm companies that met the criterias based on purposive sampling techniques. This research is descriptive research by logistic regression analysis. Developed on the study, liquidity, solvability, and profitability do not have an impact on hedging decisions simultaneously and partially.